Thermodynamic formulation of a viscoplastic constitutive model capturing unusual loading rate sensitivity. (March 2016) - Ho, Kwangsoo
Abstract: Metallic materials and alloys may exhibit serrated flow, rate insensitivity or negative rate sensitivity in a certain range of strain, strain rate and temperature. This behavior is referred to as dynamic strain aging phenomenon. A rate-dependent nonlinear kinematic hardening model was proposed byHo (2008 ) in order to model positive, zero, negative rate sensitivity of flow stress and other rate-dependent inelastic behavior in a consistent way. But it has not been demonstrated that the proposed model can be accommodated by the framework of thermodynamics of irreversible processes. The present contribution thus aims at thoroughly examining the thermodynamic consistency of the constitutive model. The evolution equations for the internal state variables are derived through the introduction of two potentials, the thermodynamic potential and the dissipation potential.